Aerosol Effects on the Atmosphere: Types, Mechanisms and Future Perspectives - Wang Yuanjie (E3S Web of Conferences)
Aerosols, composed of solid or liquid particles suspended in the atmosphere, with complex sources and mechanisms of action, are widely present in both natural environments and human activities. Aerosols directly affect the Earth’s energy balance by scattering and absorbing solar radiation and indirectly affect climate and precipitation patterns by acting as cloud condensation nuclei, altering cloud formation and microphysical properties. This paper discussed the different types of aerosols, including natural, anthropogenic, and hybrid aerosols, and analyzed their physical and chemical properties. This paper also analyzed the direct and indirect climate effects of aerosols in the atmosphere and explored future research directions, including technological innovations, interdisciplinary collaborations and international policy drivers. Future research on aerosols as an important factor in climate change will contribute to a better understanding of its complexity and to strategies to address global climate change.